Celebrating Delhi - Dayal, Mala. (New Delhi : Ravi Dayal Publisher : Penguin, Viking, 2010)
Compilation of eleven lectures delivered at the India International Centre in 2006.
Includes bibliographical references.
Keywords: Delhi (India) -- History